Systemic Therapy for Neuroendocrine Neoplasms - Chan, David L.; Singh, Simron (Digestive Disease Interventions, 2019)
Neuroendocrine neoplasms (NENs) are heterogeneous malignancies which are becoming more common. Systemic treatment is considered for patients with advanced disease, and treatment decisions are often driven by the histological grade of the tumor and the site of primary. Somatostatin analogues are the first-line option of choice for gastroenteropancreatic NENs but subsequent options may include the targeted agents everolimus and sunitinib as well as peptide receptor radionuclide therapy. Telotristat is a new option for the treatment of refractory carcinoid syndrome diarrhea. Chemotherapy is infrequently used for Grade 1 to 2 NENs (except for the combination of capecitabine and temozolomide) but is the mainstay of therapy for Grade 3 neuroendocrine carcinomas. Bronchial NENs are graded differently and there are few proven options for systemic treatment. Optimal integration of available systemic therapies, the timely recognition of tumor heterogeneity, and the use of nuclear medicine are areas of ongoing research. Finally, the patient experience is impacted by factors such as delayed diagnosis and symptoms of carcinoid syndrome. Clinicians need to account for patient priorities and disease characteristics to individualize therapy choices for patients with advanced NEN.
Keywords: neuroendocrine tumors; somatostatin; everolimus; PRRT; neuroendocrine carcinomas